Causas personales y familiares y su influencia en el abandono del tratamiento antituberculoso en los pacientes del hospital distrital "vista alegre" distrito de victor larco herrera - 2014 - Rios Vera, María Del Carmen (2014)
This research revealed the personal causes and family, and dropped out of treatment in patients in the district hospital "Vista Alegre" District Victor Larco Herrera - 2014 "; in order to determine how they influence dropped out of treatment. Taking the purpose to provide valid and reliable information so that track is achieved by the professional social work in health issues and the influence of social and family environment. The research is descriptive, methods were used: inductive - deductive, analytic - synthetic and statistical; with observation survey techniques. The present study was performed with a sampling universe of 14 patients of the Strategy for Prevention and Control of Tuberculosis. The results obtained show that personal causes that influence TB abandonment are: Irresponsibility and the level of knowledge and family reasons are: lack of family support and inadequate family environment, as it became clear that most patients have family social climate ranges from moderately favorable to unfavorable, indicating that patients do not have adequate family support for confronts her disease. In addition it was found that there is significant relationship between family social climate and dropped out of treatment, as there is a statistical and manual correlation between the two variables, so it follows that the more favorable family social climate shows there will be less frequent abandonment treatment, which emphasizes that the family plays an important role as a body of emotional support on health - disease - treatment.